Transcriptional regulation of overflow metabolism - Lim, Minqi (Nanyang Technological University, 2023)
Vibrio vulnificus causes infection of open wounds or gastrointestinal disease. It is the most lethal of the Vibrio spp. and has the highest fatality rate of any foodborne pathogen. A protozoan grazing-resistant environmental strain, ENV1 evolved to have a unique substrate preference for maximum growth. This could potentially lead to increased pathogenicity, particularly in the human gut. Hence, to understand substrate preferences, V. vulnificus ENV1 wild type, ENV1 ∆ArcA and L180 (grazing-sensitive) were grown in minimal media containing different groups of substrates. Bacteria characterization was performed in Phenotypic Microarray plates to get an overview of substrate utilization. To specify amino acids consumed during growth of ENV1, amino acid quantification was conducted via high-performance liquid chromatography. Lastly, to understand which metabolic pathways were active, we examined gene regulation using qPCR. Our results showed that ENV1 has adapted to utilize amino acids as its main carbon source. Additionally, ArcA previously known to inhibit expression of genes required for aerobic metabolism, was found to be involved in carbon source utilization, which might be regulated by NAD+/NAPH ratio. Thus, bacteria evolution studies provided us with a better understanding of the adaptations that allow them to persist in the environment and to develop as pathogens.